Anticoagulation Timing in Cardioembolic Stroke and Recurrent Event Risk. Issue 4 (5th August 2020) - Yaghi, Shadi; Trivedi, Tushar; Henninger, Nils; Giles, James; Liu, Angela; Nagy, Muhammad; Kaushal, Ashutosh; Azher, Idrees; Mac Grory, Brian; Fakhri, Hiba; Brown Espaillat, Kiersten; Asad, Syed Daniyal; et al.
Abstract : Objective: Guidelines recommend initiating anticoagulation within 4 to 14 days after cardioembolic stroke. Data supporting this did not account for key factors potentially affecting the decision to initiate anticoagulation, such as infarct size, hemorrhagic transformation, or high‐risk features on echocardiography. Methods: We pooled data from stroke registries of 8 comprehensive stroke centers across the United States. We included consecutive patients admitted with ischemic stroke and atrial fibrillation. The primary predictor was timing of initiating anticoagulation (0–3 days, 4–14 days, or >14 days), and outcomes were recurrent stroke/transient ischemic attack/systemic embolism, symptomatic intracerebral hemorrhage (sICH), and major extracranial hemorrhage (ECH) within 90 days. Results: Among 2, 084 patients, 1, 289 met the inclusion criteria. The combined endpoint occurred in 10.1% (n = 130) subjects (87 ischemic events, 20 sICH, and 29 ECH). Overall, there was no significant difference in the composite endpoint between the 3 groups (0–3 days: 10.3%, 64/617; 4–14 days: 9.7%, 52/535; >14 days: 10.2%, 14/137; p = 0.933). In adjusted models, patients started on anticoagulation between 4 and 14 days did not have a lower rate of sICH (vs 0–3 days; odds ratio [OR] = 1.49, 95% confidence interval [CI] = 0.50–4.43), nor did they have a lower rate of recurrent ischemic events (vs >14 days; OR = 0.76, 95% CI = 0.36–1.62, p = 0.482). Interpretation: In this multicenter real‐world cohort, the recommended (4–14 days) time frame to start oral anticoagulation was not associated with reduced ischemic and hemorrhagic outcomes. Randomized trials are required to determine the optimal timing of anticoagulation initiation. ANN NEUROL 2020;88:807–816